2017
DOI: 10.1177/014556131709600319
|View full text |Cite
|
Sign up to set email alerts
|

The Rising Incidence of Major Salivary Gland Cancer in the United States

Abstract: We performed a population-based historical cohort study using the Surveillance, Epidemiology, and End Results (SEER) database to determine trends in the incidence of major salivary gland cancer and to evaluate the effect of sex, tumor size, histology, primary site, and extent of disease. Participants were men and women with major salivary gland cancer, diagnosed 1973-2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 14 publications
7
48
1
Order By: Relevance
“…Furthermore, our results of the increased annual incidence of major SGC were supported the results by Boukheris et al and Signore et al who studied the SEER database during 1992‐2006 and during 1973‐2009, respectively. These results also revealed an increased incidence trend unlike other countries like Spain .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our results of the increased annual incidence of major SGC were supported the results by Boukheris et al and Signore et al who studied the SEER database during 1992‐2006 and during 1973‐2009, respectively. These results also revealed an increased incidence trend unlike other countries like Spain .…”
Section: Discussionsupporting
confidence: 92%
“…These results also revealed an increased incidence trend unlike other countries like Spain . This observation corresponds to the results reported in several other studies, including studies that reported a significant increase from 1975 to 1988 and 2005 to 2014, and other SEER‐based studies that reported an increase in incidence from 1973 to 2009 . Notwithstanding, we have found an improvement in the incidence trend of major SGC.…”
Section: Discussionsupporting
confidence: 92%
“…They account for approximately 6% of all head and neck tumors and 0.3% of all malignancies in the United States . The incidence of malignancy, however, has increased from 10.4 per 1,000,000 in 1973 to 16 per 1,000,000 in 2009 . The tumors are commonly located in parotid glands followed by the submandibular glands, the minor salivary glands, and the sublingual glands.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent SEER (Surveillance, Epidemiology, and End Results Program) database study, the incidence of major salivary gland carcinoma is increasing, particularly among small cancers. This study also demonstrated an increase in N+ and M1 cases, an increase in mucoepidermoid, acinic cell, and squamous cell carcinomas (SCCAs), and a decrease in adenoid cystic carcinomas (ACCs) and carcinoma ex‐pleomorphic adenomas over the past 36 years …”
Section: Introductionmentioning
confidence: 99%
“…This study also demonstrated an increase in N+ and M1 cases, an increase in mucoepidermoid, acinic cell, and squamous cell carcinomas (SCCAs), and a decrease in adenoid cystic carcinomas (ACCs) and carcinoma ex-pleomorphic adenomas over the past 36 years. 2 Among SGNs, parotid tumors are far more common than neoplasms in the other sites. Although parotid tumors are usually benign, the frequency of tumors overall makes the parotid gland the most common site of cancer.…”
Section: Introductionmentioning
confidence: 99%